The nexus between terrorism and organised crime: a case study of the Al-Shabaab in East Africa - Dzinoruma, Trust (Midlands State University, 2017)
The purpose of the study was to investigate into the nexus between terrorism and organized crime a case study of the Al-Shabaab in East Africa. The rationale was of that there is no nexus between terrorism and organized crime and there is the nexus between the two. The significance of the study was to enable the selected organizations in Zimbabwe and East Africa to have an insight into the relationship between terrorism and organized crime. There are no studies to the researcher’s knowledge that have carried out in Zimbabwe on the terrorism crime nexus. Also previous studies did not focus much on the nexus. The study was qualitative in nature and the purposive sampling technique was used. The researcher obtained the information required through conducting interviews and questionnaires from the respective organizations through the help of the University. The findings of the research was that there is relationship between terrorism and organized crime through poaching, piracy, drug and human smuggling, kidnappings and arms smuggling in East Africa particularly with the Al-Shabaab. Also terrorists are involved in criminal activities directly for funding their acts. The researcher would recommend that the countries involved would need to adopt and implement joint cross-border strategies that counter terrorism and combat organized crime. To future researcher would recommend that they focus much on how religion had manipulates issues of terrorism and organized crime.